Beyond Pseudo‐natural Products: Sequential Ugi/Pictet‐Spengler Reactions Leading to Steroidal Pyrazinoisoquinolines That Trigger Caspase‐Independent Death in HepG2 Cells. (31st March 2021) - Alonso, Fernando; Galilea, Agustín; Mañez, Pau Arroyo; Acebedo, Sofía L.; Cabrera, Gabriela M.; Otero, Marcelo; Barquero, Andrea A.; Ramírez, Javier A.
Abstract: In this work, we describe how stereochemically complex polycyclic compounds can be generated by applying a synthetic sequence comprising an intramolecular Ugi reaction followed by a Pictet‐Spengler cyclization on steroid‐derived scaffolds. The resulting compounds, which combine a fragment derived from a natural product and a scaffold not found in nature. are both structurally distinct and globally similar to natural products at the same time, and interrogate an alternative region of the chemical space. One of the new compounds showed significant antiproliferative activity on HepG2 cells through a caspase‐independent cell‐death mechanism, an appealing feature when new antitumor compounds are searched. Abstract : Best of both worlds : Complex polycyclic stereochemically rich compounds have been designed by connecting fragments present in bioactive natural products and bioactive synthetic molecules. One of these natural product mimics induces caspase‐independent death in human hepatocarcinoma cells.